Kaji Eksperimental Kehilangan Panas pada Dinding Ruang Bakar Fluidisasi Berbahan Bakar Biomassa - M. Faisal; Ahmad Syuhada; Hamdani Hamdani (Jurnal Teknik Mesin Unsyiah, 2014)
Biomass has several advantages, especially as it is renewable in nature. The low energy content owned by biomass requires the use of effective techniques, such as gasification. This research was to determine the rate of heat transfer that occurs in the burning of fuel in the combustion chamber fluidized types. The benefit of this research is to identify the heat loss in biomass combustion system. The fuels used in this study are wood-planed chips, branches of dry wood and areca nut husk. The size of fuel was 2 to 3 mm. The fuel was weighed to 2 kgs for one testing/biomass. The combustion duration was 50 seconds. The heat loss in biomass combustors with wood-planed chips occurred in 30 seconds at Tf 724oC and TW 203 oC, the heat loss was 26813.33 W/m. The heat loss in the combustion chamber with biomass wood-planed chips in 15 seconds at Tf-average 334 oC and Tw 44 oC, the heat loss was 2947.03 W/m. The heat loss in biomass combustors with branches of dry wood in 30 seconds at Tf 713 oC and Tw 201 oC, the heat loss was 26350.15 W/m. The heat loss in the combustion chamber with branches of dry wood biomass in 20 seconds at Tf-average 286 oC and Tw 42 oC, the heat loss was 2479.57 W/m. The heat loss in biomass combustors with areca nut husk occurred in 20 seconds at Tf 515 oC and Tw 137 oC, the heat loss was 19453.82 W/m. The heat loss in the combustion chamber with areca nut husk biomass occurred in 15 seconds at Tf- average 118 oC and Tw 39 oC, the heat loss was 802.81 W/m.